Determination of Mycophenolic Acid and Mycophenolic Acid Glucuronide Using Liquid Chromatography Tandem Mass Spectrometry (LC/MS/MS). Issue 1 (21st February 2018) - Garg, Uttam; Munar, Ada; Frazee, Clinton
Abstract: Mycophenolic acid (MPA) is an immunosuppressant that is used in renal, liver, and heart transplantation. Due to its narrow therapeutic range, monitoring of MPA levels is essential to avoid toxicity and organ rejection. Although immunoassays are available for the determination of MPA, due to their higher specificity, mass spectrometry methods are preferred. In this unit, we describe a liquid chromatography tandem mass spectrometry (LC/MS/MS) method utilizing positive ionization electrospray and multiple reaction monitoring (MRM) for the quantification of levels of MPA and its conjugate MPA glucuronide (MPAG). Blood collected in a plain, EDTA, or heparin‐containing tube is centrifuged to separate the serum or plasma. Proteins are precipitated using a solution containing zinc sulfate and acetonitrile that has been spiked with deuterated internal standards. The resulting protein‐free supernatant is injected into the LC/MS/MS system for analysis. The chromatography involves the use of a C18 column and ammonium acetate/water/formic acid and ammonium acetate/methanol/formic acid mobile phases. Quantification of MPA and MPAG levels is achieved by comparing the MRM peak area ratios of analytes and internal standards, consisting of specific precursor/product pairs, with those of calibrators at various concentrations. Calibration curves are constructed from the MRM peak area ratios of calibrators and internal standards versus concentration. © 2018 by John Wiley & Sons, Inc.